Characterization of retentive capacity of the subpericranial pocket in cochlear implants with and without a pedestal. (30th July 2015) - Papsin, Blake C.; Cushing, Sharon L.; Hubbard, Bradley J.; Wong, Daniel D. E.; Gordon, Karen A.
Abstract : Objectives/Hypothesis: To quantify the retentive capacity (RC) of the subpericranial pocket (SpP) in children undergoing cochlear implantation (CI) and measure improvements in RC with the addition of a pedestal to the device base. Retention of a CI in an SpP relies on the integrity of surrounding tissues to determine device position and resist movement from external forces. We hypothesize that device position can be controlled and resistance to movement can be improved with placement of a small pedestal on the base of the CI receiver stimulator. Study Design: Analysis of prospectively assembled data. Methods: Ninety‐seven patients (145 devices) underwent CI (48 bilateral, 49 unilateral). Intraoperatively, a force gauge measured the displacement force on a template Nucleus 5 (Cochlear Corporation, Sydney, Australia) implant placed in an SpP prior to routine suture fixation of a standard device. In 47 patients (64 devices), displacement forces were also measured for a custom template Nucleus 5 implant with pedestal. Results: Average RC of the SpP for the standard device was 5.59 N ± 2.73 standard deviation (SD), which increased to 9.401 N ± 4.6267 SD with a pedestaled device. Resistance to displacement decreased significantly across trials in both groups ( P <.0001). Retentive capacity of the SpP increased significantly with the addition of a pedestaled device ( P  < .0001). The interaction between device and trial was also found to be significant ( P  = .05). Conclusions: The RC of the SpP in children and the ability to resist device migration in the absence of fixation may improve with the addition of a pedestal attached to the device. Level of Evidence: 2b. Laryngoscope, 126:1175–1179, 2016